REVOLUTIONIZING MOTHER TONGUE AND LITERATURE CLASSES: AN INNOVATIVE APPROACH FOR EFFECTIVE ORGANIZATION - Tokhtayeva Nargiza Narziyevna (Galaxy International Interdisciplinary Research Journal, 2023)
The organization of mother tongue and literature classes is crucial for providing students with a solid foundation in language skills, cultural understanding, and critical thinking. Traditional teaching methods often fall short of engaging students and maximizing their learning potential. Therefore, this scientific article proposes an innovative approach to organizing mother tongue and literature classes, leveraging modern educational theories, interdisciplinary techniques, and technology integration. This approach aims to create an engaging and interactive learning environment that fosters creativity, analytical thinking, and cultural appreciation.